THE EFFECTS OF EMOTIONAL REGULATION TRAINING ON COGNITIVE REAPPRAISAL AND EXPRESSIVE SUPPRESSION AMONG WORKERS IN BANGKOK - Taesillapasathit, Tanprang; Menon Arikkatt, Rajitha (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
Background: Emotional regulation issues are critical factors in mental health, often leading to heightened negative emotions and psychiatric symptoms. This study investigates the effectiveness of an emotional regulation intervention in improving emotional regulation strategies, specifically cognitive reappraisal, and expressive suppression, among professional workers in Bangkok, Thailand. Method: A randomized pretest-posttest control group design was used. Eighty-two professional workers (N= 80) were randomly assigned to either an intervention group or a control group. The intervention consisted of five weekly group sessions focusing on emotional regulation skills, utilizing a combination of Dialectical Behavior Therapy (DBT) and Acceptance and Commitment Therapy (ACT). Cognitive reappraisal and expressive suppression were measured using the Emotion Regulation Questionnaire (Gross & John, 2003). Results: The intervention group showed significant improvements in emotional regulation, with increased use of cognitive reappraisal and decreased reliance on expressive suppression compared to the control group. These findings suggest that the emotional regulation intervention effectively enhanced participants’ ability to manage their emotional responses in the workplace. Conclusion: Emotional regulation training significantly improves emotional regulation strategies among professional workers, highlighting the potential benefits of incorporating such interventions into workplace wellness programs. This can lead to better emotional well-being and more effective management of workplace stressors.